Construction of movement-sleep-study (MSS) collaborative intervention model based on biological rhythm regulation - BINYANG LI (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Biological rhythms regulating movement, sleep, and study significantly impact cognitive function and academic performance. However, conventional educational models often overlook their integration, leading to cognitive fatigue and reduced learning efficiency. This study develops and evaluates the Movement-Sleep-Study (MSS) collaborative intervention model, designed to synchronize these rhythms for optimized learning.